Geographical analysis of climate vulnerability at a regional scale: the case of the Southern Great Plain in Hungary - Farkas, Jenő Zsolt; Hoyk, Edit; Rakonczai, János (Hungarian Geographical Bulletin, 2017)
This paper provides an example for regional scale analysis of climate vulnerability incorporating environmental as well as socio-economic indicators. Researches have focused on different aspects of climate vulnerability so far, but usually there is little connection between the physical and social dimensions. Our study provides a more complex analysis, which builds on the application of international indices which have been used on the local and regional levels very rarely. In our research we combined physical and human geographical approaches and research techniques. The physical geographical assessment is based on indicators referring to ground water levels and vegetation production, while the human geographical side of the analysis focuses on economic and social sensitivity, adaptation and exposure indices, combined in the so-called socio-economic climate vulnerability index. In the analysis we tried to figure out the most sensitive areas in the Hungarian Southern Great Plain region. The main findings of the study are "hot spots" which coincide on both analyses, therefore, the most sensitive areas under current climate change conditions could be delimited. This study also demonstrates that the resolution of global climate change vulnerability indices is not suitable for regional scale analysis because of the significant territorial differences. Therefore, local or regional scale assessments are needed for the preparation of strategies for the elaboration of mitigation and adaptation policies.